Molecular dynamics of Lys49 PLA2-like toxins: Insights into solution and membrane-bound conformations - Santos Rachão, Rui Pedro (2025)
Snakebite envenoming is a neglected tropical disease that causes death and disability. Lysine 49 phospholipase A2-like (Lys49 PLA2-like) proteins are abundant toxins in many viperid venoms and play a significant role in their toxicity. They induce skeletal muscle necrosis by disrupting the plasma membrane through a mechanism independent of phospholipid hydrolysis. X-ray structures of Bothrops asper Lys49 PLA2-like proteins were analysed for sequence, folding and quaternary structure, and compared with dimer geometries of Lys49 PLA2s from other viper species in the PDB. Sequence and folding were mainly conserved, whilst quaternary structure was not. With a single exception, all quaternary structures fell into two categories: compact and extended. The B. asper extended and compact Lys49 PLA2 conformations were simulated in solution and in a membrane bilayer with molecular dynamics and scrutinised in light of mechanistic proposals and experimental data. Both conformations dissociated into monomers in solution. Membrane binding was more stable with higher fractions of negatively charged phospholipids, achieved through the inclusion of DMPA. The extended dimer desorbed in pure POPC, kept its dimeric conformation when adsorbed to POPC/DMPA (9:1), and dissociated into monomers in POPC/DMPA (1:1). Still, the protein remained adsorbed in the latter case. The compact dimer desorbed from the membrane in the pure POPC bilayer, lost its conformation in POPC/DMPA (1:1), and dissociated into monomers in a POPC/DMPA (9:1) composition. The monomers oscillated between vertical (compact-like) and horizontal (extended-like) orientations. These scenarios show that the current hypotheses for the membrane disruption mechanism by Lys49 PLA2-like proteins are not entirely aligned with the evidence, and alternative possibilities need to be considered. Our observations suggest that Lys49 PLA2s could act as monomers but may also associate into higher-order oligomers during membrane interaction. This highly complex molecular scenario aligns with recent evidence indicating that the membrane promotes protein oligomerisation.